2019
DOI: 10.5144/0256-4947.2019.265
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of apixaban for stroke prevention in non-valvular atrial fibrillation in Saudi Arabia

Abstract: BACKGROUND: Apixaban, an oral anticoagulant for stroke and systemic embolism prevention in non-valvular atrial fibrillation (NVAF), was superior to warfarin in prevention of stroke and systemic embolism, bleeding outcomes and mortality (ARISTOTLE trial), and substantially reduced stroke risk, with no significant increase in major or intracranial bleeding risk versus aspirin (AVERROES trial).OBJECTIVE: Estimate cost-effectiveness of apixaban versus other anticoagulants for NVAF treatment in Saudi Arabia.DESIGN:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…Two studies did not report the perspective of the analysis. 18 , 19 The majority of the studies evaluated costs from the health-care system perspective, which refers to a variety of bodies, including hospitals (n = 8) 17 , 20 , 23 , 24 , 26 , 27 , 29 , 30 or public payers (n = 1), 28 with one additionally considering the societal perspective. 30 Societal (n = 2) 22 , 25 and patient (n = 1) 21 perspectives were also adopted.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies did not report the perspective of the analysis. 18 , 19 The majority of the studies evaluated costs from the health-care system perspective, which refers to a variety of bodies, including hospitals (n = 8) 17 , 20 , 23 , 24 , 26 , 27 , 29 , 30 or public payers (n = 1), 28 with one additionally considering the societal perspective. 30 Societal (n = 2) 22 , 25 and patient (n = 1) 21 perspectives were also adopted.…”
Section: Resultsmentioning
confidence: 99%
“…Warfarin and DOAC are nationally approved in Saudi Arabia. Patient information leaflets were evaluated for the recommended intake regimen of all five anticoagulants (warfarin: QD only, dabigatran: BID only, apixaban: BID only, rivaroxaban: QD only, and edoxaban: QD only) [13][14][15].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, NOACs are more cost-effective than Warfarin, as demonstrated by a study conducted in 2019 studying the cost-effectiveness of apixaban for stroke prevention in non-valvular atrial fibrillation in Saudi Arabia [ 9 ]. Since NOACs were released in the market they have been increasingly used to prevent stroke in atrial fibrillation patients, an observational study was conducted by (Boriani et al in 2018) to assess prevention strategies in 27 European countries, concluded that between 2013-2016 the patients who were on OACs therapy were much more than those who were on antiplatelet therapy and that NOAC accounted for 40.9% of OACs.…”
Section: Introductionmentioning
confidence: 99%